Mechanisms of synaptic depression triggered by metabotropic glutamate receptors - Bellone, C; Lüscher, C; Mameli, M (Cellular and molecular life sciences : CMLS, 2008)
Glutamate, by activation of metabotropic receptors (mGluRs), can lead to a reduction of synaptic efficacy at many synapses. These forms of synaptic plasticity are referred to as long-term depression (mGluR-LTD). We will distinguish between mGluR-LTD induced by pre- or postsynaptic receptors and mGluR-LTD induced by the locus of the expression mechanism of the synaptic depression. We will also review recent evidence that mGluR-mediated responses themselves are subject to depression, which may constitute a form of metaplasticity.